2019
DOI: 10.1590/s1677-5538.ibju.2018.0737
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endovascular treatment of renal arterial stenosis in transplanted kidneys

Abstract: Objective To evaluate the effectiveness and outcomes of endovascular treatment of TRAS with PTA.Materials and Methods We searched our prospectively collected database looking at cases of TRAS between January 2005-December 2011. CCT was the gold-standart for diagnosis of TRAS. Parameters analysed comprised technical aspects, arterial blood pressure variation, and renal function. A minimum follow-up of 24 months was considered.Results Of the 2221 renal transplants performed in the selected period, 22 (0.9%) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Only 35 studies provided enough data for meta-analysis. An overall summary of the included studies, size, and evidence grading can be found in Supplemental Table S1 2,4,7,12,27-77 . We propose a diagnostic and therapeutic algorithm that reflects the findings, which is displayed in Figure 2 on the basis of the frequency of reporting cutoff parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Only 35 studies provided enough data for meta-analysis. An overall summary of the included studies, size, and evidence grading can be found in Supplemental Table S1 2,4,7,12,27-77 . We propose a diagnostic and therapeutic algorithm that reflects the findings, which is displayed in Figure 2 on the basis of the frequency of reporting cutoff parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment measures for TRAS include optical medical administration alone, surgical revascularization and percutaneous transluminal angioplasty with or without stenting[ 14 ]. As a less invasive approach than surgery, percutaneous transluminal angioplasty with stenting has become the first-line option without the support of very strong evidence[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug treatment could control renovascular hypertension, but it could not prevent the progression of RAS. PTRA could significantly improve renal blood flow and reduce blood pressure, also ensure the functionality of the graft and normalization of renal function, 9 while surgery is only performed when contraindications for PTRA exists.…”
Section: Discussionmentioning
confidence: 99%